Assessment of shear strength of interior reinforced concrete beam-column joint - Gbree, Abrham; Segni , Getu; Fikadu , Garomsa (Zede Journal of Ethiopian Engineers and Architects, 2023)
Even though beam-column joint is one of the most critical regions in reinforced concrete (RC) frames used to transfer loads from beam to column, a little attention is paid to its design in Ethiopian practice. In this paper, shear strength of an interior beamcolumn joint of a RC building frame designed to the old code (EBCS 2, 1995) has been investigated. The building is analyzed for seismic actions and the shear strength of the beam-column joint is estimated using both empirical expressions and analytically by using a finite element (FEM) modeling program. The interior joint of a RC frame is selected to be assessed under monotonic loading for a constant column axial load. The study showed that there is a significant variation between the results from numerical analysis using VecTor2 and provisions in ESEN1998-1-2015. From the investigation, it is observed that the interior joint satisfies both ductility and shear strength requirements after the column has been strengthened by concrete jacketing. This study is not enough in exposing the problems regarding design and detailing of beam-column joints in Ethiopian code of practice. Laboratory investigation is highly recommended due to its accuracy compared to numerical simulations.